Origin and driving mechanisms of marine litter in the shelf-incised Motril, Carchuna, and Calahonda canyons (northern Alboran Sea) - Cerrillo-Escoriza, Javier; Lobo, Francisco José; Puga-Bernabéu, Ángel; Rueda, José Luis; Bárcenas, Patricia; Sánchez-Guillamón, Olga; Serna Quintero, José Miguel; Pérez Gil, José Luis; Murillo, Yelvana; Caballero-Herrera, José Antonio; López-Quirós, Adrián; Mendes, Isabel; et al. (Frontiers in Marine Science, 2023)
Introduction and methods Marine litter density, distribution and potential sources, and the impact on canyon seafloor habitats were investigated in the Motril, Carchuna and Calahonda canyons, located along the northern margin of the Alboran Sea. During the ALSSOMAR-S2S oceanographic survey carried out in 2019, canyon floor imagery was collected by a Remotely Operated Vehicle along 5 km in the Motril Canyon, 10 km in the Carchuna Canyon, and 3 km in Calahonda Canyon, together with 41 surficial sediment samples. Additionally, coastal uses, maritime traffic and fishing activity data were analyzed. A 50 m resolution multibeam bathymetry served as base map. Results In the Motril and Calahonda canyons, the density of marine litter was low and the material was dispersed, very degraded and partially buried. In contrast, the Carchuna Canyon contained a greater amount and variety of litter. The Carchuna Canyon thalweg exhibited a density of marine litter up to 8.66 items·100 m-1, and litter hotspots with a density of up to 42 items·m2 are found along the upper reaches of the canyon thalweg. Discussion Low litter abundances found in the studied canyons most likely reflect low population densities and the absence of direct connections with streams in the nearby coasts. The high shelf incision of the Carchuna Canyon and its proximity to the coastline favor littoral sediment remobilization and capture as well as the formation of gravity flows that transport the marine litter along the thalweg toward the distal termination of the channel. Litter hotspots are favored by the canyon morphology and the occurrence of rocky outcrops. Most debris is of coastal origin and related to beach occupation and agricultural practices in the adjacent coastal plain. A third origin was represented by fishing gear in the study area. Fishing activity may be producing an impact through physical damage to the skeletons of the colonial scleractinians located in the walls of the Carchuna Canyon. In contrast, the Motril and Calahonda canyons can be considered passive systems that have mainly acted as depositional sinks in the recent past, as evidenced by buried marine litter.